Assessment of a model for achieving competency in administration and scoring of the WAIS-IV in post-graduate psychology students - Roberts, Rachel M.; Davis, Melissa C. (Frontiers in Psychology, 2015)
There is a need for an evidence-based approach to training professional psychologists in the administration and scoring of standardized tests such as the Wechsler Adult Intelligence Scale (WAIS) due to substantial evidence that these tasks are associated with numerous errors that have the potential to significantly impact clients’ lives. Twenty three postgraduate psychology students underwent training in using the WAIS-IV according to a best-practice teaching model that involved didactic teaching, independent study of the test manual, and in-class practice with teacher supervision and feedback. Video recordings and test protocols from a role-played test administration were analyzed for errors according to a comprehensive checklist with self, peer, and faculty member reviews. 91.3% of students were rated as having demonstrated competency in administration and scoring. All students were found to make errors, with substantially more errors being detected by the faculty member than by self or peers. Across all subtests, the most frequent errors related to failure to deliver standardized instructions verbatim from the manual. The failure of peer and self-reviews to detect the majority of the errors suggests that novice feedback (self or peers) may be ineffective to eliminate errors and the use of more senior peers may be preferable. It is suggested that involving senior trainees, recent graduates and/or experienced practitioners in the training of postgraduate students may have benefits for both parties, promoting a peer-learning and continuous professional development approach to the development and maintenance of skills in psychological assessment.